Revisiting the Principle of Ultimum Remedium in Criminal Law Reform: A Human Rights Perspective on the Indonesian New Penal Code - Fiona Mae Gallagher (Vifada Assumption Journal of Law, 2025)
This article revisits the principle of ultimum remedium in the context of Indonesia’s new Penal Code, examining how the state’s renewed approach to criminalization aligns with contemporary human rights standards. Although ultimum remedium positions criminal law as a last resort, recent legal reforms demonstrate both expansion and recalibration of state punitive power. Through doctrinal analysis and a human-rights–based lens, this study evaluates whether the new Penal Code sufficiently limits over-criminalization, ensures proportionality, and incorporates alternative mechanisms such as administrative sanctions, restorative justice, and diversion. Particular attention is given to provisions that affect civil liberties, including morality-based offenses, expression-related crimes, and community-order regulations, which may conflict with international human rights norms on freedom, privacy, and legal certainty. The findings reveal a persistent tension between the government’s aims to maintain social order and the obligation to protect individual rights. While the new Penal Code introduces certain progressive elements, inconsistencies in the application of ultimum remedium risk perpetuating punitive excess and selective enforcement. The article argues that a rights-centered approach to criminal law reform requires clearer thresholds for criminalization, enhanced judicial oversight, and integration of non-penal policy pathways. Ultimately, strengthening the ultimum remedium principle is essential for ensuring that Indonesia’s criminal justice system remains both effective and rights-respecting.